2019
DOI: 10.5080/u23677
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lithium on Calcium and Parathormone Levels: A Cross-sectional Study with Healthy Controls

Abstract: Lityum ile ilişkili hiperparatiroidi (LİH) pek çok olumsuz tabloya neden olabilmekteyken yeteri kadar üzerinde durulan bir yan etki değildir. Bu çalışmanın amacı lityumun kalsiyum ve parathormon üzerine etkisini ve LİH ile tiroid hastalıkları arasındaki ilişkiyi incelemektir. Yöntem: Bu kesitsel çalışmaya, lityum kullanan 87 bipolar bozukluk tanılı hasta ve lityum grubu ile yaş ve cinsiyet açısından benzer 65 sağlıklı gönüllü alınmıştır. Katılımcıların kalsiyum, intakt parathormon, fosfor, magnezyum, alkalen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…On the 7th day of the supportive treatment for lithium poisoning, TSH was 3.56 mIU/L, and this value is maintained in the ongoing follow-ups of the patient, and the patient did not receive thyroid replacement therapy. In addition, the incidence of hypercalcemia due to lithiumassociated hyperparathyroidism (LIH) was found in a wide range of 3.6-62% (22). In our case, PTH and serum calcium levels were within normal limits.…”
Section: Discussionmentioning
confidence: 54%
“…On the 7th day of the supportive treatment for lithium poisoning, TSH was 3.56 mIU/L, and this value is maintained in the ongoing follow-ups of the patient, and the patient did not receive thyroid replacement therapy. In addition, the incidence of hypercalcemia due to lithiumassociated hyperparathyroidism (LIH) was found in a wide range of 3.6-62% (22). In our case, PTH and serum calcium levels were within normal limits.…”
Section: Discussionmentioning
confidence: 54%
“…[17,18] A previous study also showed that potential deleterious conditions can be prevented by assessing PTH and calcium levels before and during lithium therapy. [19] The aim of this research was to investigate the endocrinological effects of experimental subacute lithium application at different concentrations on serum T3, T4, TSH, PTH and calcium levels and thyroid tissue and to reveal the relations between them. Our research is also important as one of the rare biochemical analyses of these hormones and histological examinations of thyroid tissue.…”
Section: Introductionmentioning
confidence: 99%